KAJIAN POLITIK HUKUM TERHADAP PENGUATAN SISTEM PRESIDENSIIL DI INDONESIA - , LUTU DWI PRASTANTA, Prof. Dr. Sudjito, SH., M.Si. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Reforms era taking place in Indonesia in 1999 has led to many changes, one of which changes in the constitutional practice in Indonesia. After the authoritarian New Order, hopes to establish a base of power through the 1945 amendment is the only way, but to improve the existing systems by eliminating one by one the great authority of the executive power of government to be confused when they agreed to form a presidential system, and changes that occurs leads to \"quasi-presidential\" which further strengthens the position of the parliament. The explanation of the question can be raised whether political variables significantly influence the strengthening of Indonesia's presidential system. The purpose of this study was to determine whether political variables significantly influence the strengthening of the Presidential system. This research is a normative and empirical, while in terms of the characteristic of the report is a descriptive study. Descriptive mean this study are expected to provide a comprehensive and systematic overview of political of law on strengthening presidential system in Indonesia. The analytical results of this study were obtained from an analysis of the case. Results of this research are political variables affect the strengthening of the presidential system, in this case can be seen starting from the 1999 election by 48 political parties, elections 2004, followed by 24 political parties, elections 2009 party attended by 38 national and 6 local parties, and elections 2014 attended 12 national party and 3 local party. The number of the political party influence the presidential system because the presidential system which is applied in the multi-party system cause conflict between the executive and the legislature and made democracy unstable. The most significantly affect the strengthening of the presidential system is a political party, which political party is in a position input and conversion. Aggregating the input position in terms of that it represents the interests of society while converting a position of political parties to articulate the interests of public policy to be product. Recommendations from this study is the simplification of the number of political parties and the rearrangement of the law and building the permanent coalition.